Protein Biochemistry and Expression Regulation of Cadmium/Zinc Pumping ATPases in the Hyperaccumulator Plants Arabidopsis halleri and Noccaea caerulescens - Mishra, Seema; Mishra, Archana; Küpper, Hendrik (Frontiers in Plant Science, 2017)
P1B-ATPases are decisive for metal accumulation phenotypes, but mechanisms of their regulation are only partially understood. Here we studied the Cd/Zn transporting ATPases NcHMA3 and NcHMA4 from Noccaea caerulescens as well as AhHMA3 and AhHMA4 from Arabidopsis halleri. Protein biochemistry was analysed on HMA4 purified from roots of N. caerulescens in active state. Metal titration of NcHMA4 protein with an electrochromic dye as charge indicator suggested that HMA4 reaches maximal ATPase activity when all internal high-affinity Cd2+ binding sites are occupied. Although HMA4 was reported to be mainly responsible for xylem loading for heavy metals for root to shoot transport, the current study revealed high expression of NcHMA4 in shoots as well. Further, there were additional 20 kD and 40 kD fragments at replete Zn2+ and toxic Cd2+, but not at deficient Zn2+ concentrations. Altogether, the protein level expression analysis suggested a more multifunctional role of NcHMA4 than previously assumed. Organ-level transcription analysis through quantitative PCR of mRNA in N. caerulescens and A. halleri confirmed the strong shoot expression of both NcHMA4 and AhHMA4. Further, in shoots NcHMA4 was more abundant in 10 µM Zn2+ and AhHMA4 in Zn2+ deficiency. In roots, NcHMA4 was up-regulated in response to deficient Zn2+ when compared to replete Zn2+ and toxic Cd2+ treatment. In both species, HMA3 was much more expressed in shoots than in roots, and HMA3 transcript levels remained rather constant regardless of Zn2+ supply, but were up-regulated by 10 µM Cd2+. Analysis of cellular expression by quantitative mRNA in situ hybridisation (QISH) showed that in A. halleri, both HMA3 and HMA4 mRNA levels were highest in the mesophyll, while in N. caerulescens they were highest in the bundle sheath of the vein. This is likely related to the different final storage sites for hyperaccumulated metals in both species: epidermis in N. caerulescens, mesophyll in A. halleri.